2016
DOI: 10.1002/anie.201602644
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Drug Metabolites via Transition‐Metal Catalyzed C−H Oxidation: The Liver as Synthetic Inspiration

Abstract: Can classical and modern chemical C-H oxidation reactions complement biotransformation in the synthesis of drug metabolites? We have surveyed the literature in an effort to try to answer this important question of major practical significance in the pharmaceutical industry. Drug metabolites are required throughout all phases of the drug discovery and development process; however, their synthesis is still an unsolved problem. This Review, not intended to be comprehensive or historical, highlights relevant appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 166 publications
0
80
0
2
Order By: Relevance
“…Methods for efficient and selective alkyl C–H oxidation could streamline the synthesis of fine chemicals, natural products, and drug metabolites. 1 , 2 Despite rapid advances in the development of metal-catalyzed reactions 3 and reagents, 4 synthetically useful C(sp 3 )–H oxygenation chemistry is still in great demand. 5 , 6 Recently, radical reactions mediated by hypervalent iodine( iii ) reagents have emerged as viable means to oxygenate C(sp 3 )–H bonds under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for efficient and selective alkyl C–H oxidation could streamline the synthesis of fine chemicals, natural products, and drug metabolites. 1 , 2 Despite rapid advances in the development of metal-catalyzed reactions 3 and reagents, 4 synthetically useful C(sp 3 )–H oxygenation chemistry is still in great demand. 5 , 6 Recently, radical reactions mediated by hypervalent iodine( iii ) reagents have emerged as viable means to oxygenate C(sp 3 )–H bonds under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[49] TourØ et al identified aCuI/air system to oxidize tertiary amines a to the nitrogen. [51] Lactam/ amide formation and N-dealkylation via subsequent hydrolysis were the main reactions observed, but CÀCb ond cleavage in oxalamide fragments and on tertiary carbons, initiated via benzylic oxidation, were also seen depending on the substrate.T hough selectivity was not an aim it nicely illustrates chemoselectivity to be one of the big challenges in aerobic oxidations. In this way am imic of cytochrome P450s and alcohol/aldehyde dehydrogenases was achieved.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…Failure to elucidate all of the key metabolic processes the NCE undergoes can lead to patient (or unborn child) safety risks, fatalities and market withdrawal of the drug. Metabolism encompasses all of the chemical and redox reactions involved in the biotransformation of a drug within the body …”
Section: Introductionmentioning
confidence: 99%
“…Metabolism encompasses all of the chemical and redox reactions involved in the biotransformation of a drug within the body. [2] The ultimate purpose of metabolism is to convert a drug into a more polar form that can be cleared (eliminated) from the body. Clearly a balance needs to be struck between lack of metabolism (drug accumulation), desired metabolism (e. g. prodrug release) and rapid metabolism (short half-life / duration of action) depending on the drug target.…”
Section: Introduction To Drug Metabolismmentioning
confidence: 99%